1973
DOI: 10.1159/000224811
|View full text |Cite
|
Sign up to set email alerts
|

Calusterone (7β,17α-DimethyItestosterone) as Primary and Secondary Therapy of Advanced Breast Cancer

Abstract: The antitumor efficacy of calusterone, 200 mg/day by mouth, against objectively progressing advanced breast cancer was evaluated by the Cooperative Breast Cancer Group criteria in 117 women. In 41, calusterone was the first treatment for advanced breast cancer, in 49 it was given as secondary steroidal therapy, and in 27 it followed cytotoxic chemotherapy. Part of the study included comparison by the double-blind technique of calusterone in 23 women with Δ1-testololactone, 1,000 mg/day by mouth, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…In contrast to the 32% regression rate obtained with the Upjohn tablets of AMestololactone, l,000/day,as primary hormonal therapy, the samepreparation produced only one regression in 12 previously treated women (8%) [12]. We thus confirm the claim of Segaloff et ai [18] that AMestololactone is a potent antitumor agent when used as primary therapy against advanced fe male breast cancer.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast to the 32% regression rate obtained with the Upjohn tablets of AMestololactone, l,000/day,as primary hormonal therapy, the samepreparation produced only one regression in 12 previously treated women (8%) [12]. We thus confirm the claim of Segaloff et ai [18] that AMestololactone is a potent antitumor agent when used as primary therapy against advanced fe male breast cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Subse quently, The Upjohn Co. prepared for us compressed tablets of AMestololactone with T50 of 4.5 to 8.5 min. When tested for antitumor efficacy against advanced breast cancer in women without previous hormonal or chemothera py, using a dose of 1,000 mg/day by mouth, the Upjohn preparation pro duced regressions in 8 of 25 women (32%) [12]. In this study, A'-testololactone was double-blinded against calusterone, 200 mg/day by mouth, which produced 12 regressions in 23 women (52%).…”
Section: Discussionmentioning
confidence: 79%
“…Subsequently, the use of testosterone propionate, the testosterone derivative fluoxymesterone and the steroid calusterone obtained promising results in terms of disease response and pain relief in patients with metastatic BC (MBC) whose hormone receptor status was unknown (Segaloff et al 1951, Kennedy 1958, Goldenberg 1964, Goldenberg et al 1973, Gordan et al 1973). More recently, Boni et al reported a significant therapeutic activity of testosterone propionate in a consecutive series of 53 patients with ER/PgR-positive MBC (Boni et al 2014).…”
Section: Ar-targeting Therapy In Bcmentioning
confidence: 99%
“…In breast cancer cells, androgens, such as 5a-dihydrotestosterone and its precursors androstenedione and testosterone, have inhibitory effects (2-9), whereas estrogens, such estradiol, have mitogenic effects. In fact, testosterone propionate, fluoxymesterone, and calusterone were previously used in the adjuvant therapy of breast cancer in both premenopausal and postmenopausal women with an efficacy comparable to that achieved with other types of endocrine manipulations, such as tamoxifen (10)(11)(12)(13). The androgen receptor (AR) is present in 50% to 90% of breast tumors (14), and the AR levels are closely correlated with the content of estrogen receptor (ER) and progesterone receptor.…”
Section: Introductionmentioning
confidence: 99%